POTENSI MINYAK KAYU PUTIH (Melaleuca cajuputi) SEBAGAI SUMBER BAHAN AKTIF DALAM PEMBUATAN HAND SANITIZER LIDAH BUAYA - Nursanti Yuliani; Sophia Grace Sipahelut; Vita Novalin Lawalata (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
Hand sanitizer as a medium to maintain hand hygiene is becoming a trend among the community today, especially because of the COVID-19 pandemic. Hand sanitizers with active ingredients of essential oils are considered safer than alcohol. The purpose of this research was to examine the addition of cajuput oil in the manufacture of aloe vera hand sanitizer on the physical quality, antiseptic and organoleptic activity of the hand sanitizer produced. The research design used a completely randomized design (CRD) with one factor, namely the addition of cajuput oil, with five treatment levels, namely 0 mL, 16 mL, 20 mL, 24 mL, and 28 mL with each treatment in three replications. The hand sanitizer produced was then tested for physical characteristics (density, spreadability, pH, and homogeneity), antiseptic activity, and organoleptic characteristics (color, texture, aroma and non-sticky impression). The results showed that the aloe vera hand sanitizer sample with the addition of 28 mL cajuput oil had a stronger antiseptic effectiveness among other samples and had physical characteristics that met the quality requirements of SNI hand sanitizer including pH 7.33, spreadability 6.96 cm, density 1.1546, homogeneous without any coarse grains and organoleptically acceptable and favored by the panelists.